Effect of boscalid on podtharvest decay of strawberry caused by Botrytis cinerea and Rhizopus stolonifer - Salato, B.V.=700 1 Torres, R.; Zoffoli, J.P.; Latorre, B.A.
(Es, En)
ilus., 35 ref.
Keywords: TERAPIA; PODREDUMBRES; FRESA; ENFERMEDADES POSTCOSECHA; BOTRYTIS CINEREA; RHIZOPUS STOLONIFER; CONTROL DE ENFERMEDADES; FUNGICIDAS; ESPAÑA; BOSCALID